Glycosylation in T2 high and Th17 Asthma: A Narrative Review - Yuan X; Li C; Gao J; Yang L; Wang B; Li Z (Journal of Asthma and Allergy)
Xingxing Yuan,1,2 Chaofan Li,1 Jiawei Gao,1 Liuxin Yang,1 Bingyu Wang,2 Zhuying Li3 1First Clinical Medical College, Heilongjiang University of Chinese Medicine, Harbin, People’s Republic of China; 2Department of Medicine, Heilongjiang Academy of Traditional Chinese Medicine, Harbin, People’s Republic of China; 3Department of Respiratory, First Affiliated Hospital of Heilongjiang University of Chinese Medicine, Harbin, People’s Republic of ChinaCorrespondence: Bingyu Wang, Department of Medicine, Heilongjiang Academy of Traditional Chinese Medicine, No. 33 Xidazhi Street, Nangang District, Harbin, Heilongjiang, 150006, People’s Republic of China, Email wangbingyu1984@sina.com Zhuying Li, Department of Respiratory, First Affiliated Hospital of Heilongjiang University of Chinese Medicine, No. 24 heping Street, Xiangfang District, Harbin, Heilongjiang, 150040, People’s Republic of China, Email lizhuying2025@126.comAbstract: Glycosylation, a fundamental biochemical process, entails the covalent attachment of sugar molecules to proteins, DNA, or RNA. Beginning with an overview of the pathophysiological features of asthma, this review proceeds to elucidate various facets of glycosylation in asthma pathology, specifically in T2 high asthma and Th17-mediated responses. We examined glycosylation’s involvement in regulating airway inflammation, encompassing the modulation of pro-inflammatory cytokine release such as IL-4, IL-5, and IL-13, key components of T2 inflammation, as well as its significance in modulating immune cell functionality, notably T cells and dendritic cells. Moreover, we explored glycosylation’s impact on airway remodeling processes, including its regulation of airway smooth muscle cell proliferation and migration. Addressing molecular mechanisms, this review delved into several glycosylation modifications of proteins and genes implicated in asthma pathogenesis, including IgE, IL-4 receptor, TGF-β, and the regulation of select glycosylation enzymes. Additionally, the review highlights the role of Th17 cells in T2 high asthma and their modulation through glycosylation. We underscored future research imperatives, including biomarker discovery, therapeutic realization, and the potential utility of glycosylation modifications in asthma prevention and management. In short, this review provides an in-depth analysis of the critical role of glycosylation in the pathogenesis of T2 high asthma and Th17 responses.Keywords: glycosylation, asthma, airway inflammation, airway remodeling, immunity